Identification of major QTLs for seed size by combining QTL-mapping and RNAseq in an electron beam induced mutant of groundnut (Arachis hypogaea L.): Identification of major QTLs for seed size by combining QTL-mapping and RNAseq in an electron beam induced mutant of groundnut (Arachis hypogaea L.) - POONAM G BHAD; SUVENDU MONDAL; ANAND M BADIGANNAVAR (Journal of Oilseeds Research, 2023)
Combining QTL-mapping using SNP markers generated with genotyping by sequencing and RNA-seq identified a major QTL and candidate genes for enhanced seed size and leaf size in groundnut, respectively. Towards this, we conducted quantitative trait locus (QTL) analysis for hundred kernel weight in F2 mapping population derived from electron beam induced large seed mutant, TG 89 and normal seed genotype, ICGV 15007. A major QTL for seed size was identified in Arahy.05 chromosome between flanking markers AhMITE470 and SNP05_103140987. This QTL interval harboured a groundnut ortholog of TIFY gene. Of the 29 TIFY family genes in groundnut, the gene arahy.5M7JWE is the identified within the QTL interval on chromosome A05 and was down regulated in the mutant, indicating its putative role for large seed phenotype in the mutant.